PELATIHAN ECO ENZYME SEBAGAI ALTERNATIF PENGELOLAAN SAMPAH ORGANIK KULIT BUAH TINGKAT SLTA KECAMATAN LAWANG KIDUL - Putra, Putra; Sarmidi, Sarmidi; Fadhilah, Astrid; Nurbaiti, Nurbaiti; Mases, Yulius (Batara Wisnu : Indonesian Journal of Community Services, 2024)
Organic waste management remains a significant environmental challenge, particularly in Lawang Kidul District, where the volume of fruit peel waste continues to increase. This study aims to provide eco-enzyme production training to high school students as an alternative solution for managing organic waste. The methods used include workshops, hands-on practice, and mentoring throughout the three-month fermentation process of eco enzyme. The results showed a success rate of 85.71%, with an average final pH of 3.735 in the first bottle and 3.77 in the second bottle. The produced eco enzyme has potential applications as a natural cleaner, liquid organic fertilizer, and disinfectant. This activity successfully increased students’ awareness of the importance of organic waste management and provided practical skills that can be applied at home and in school environments.